Rice strategy: Improving sustainable halal agri-food system through green marketing and shifting consumer behavior with a quintuple helix approach - Dwiyani, Dewa Ayu Made Safira; Sanneh, Kally; Murheza, Kevin; Khairani, Najwa Azka; Lubis, Rifaldy Setiawan; Darmawan, Noviyan (Halal Studies and Society, 2025)
This study aimed to examine the role of RICE strategy (Reinforcement, Influence, Collaboration, and Evolution) in enhancing the sustainability of halal agri-food systems through green marketing and shifting consumer behavior. The significance of halal certification and the growing demand for sustainable food products was examined in the context of Indonesia predominantly Muslim population. The methodology combined a literature review and case study analysis to explore the contributions of various stakeholders including government, academia, industry, civil society, and the environment toward improving halal food production systems. Technological integration, including blockchain, IoT, Lean Knowledge Management (LKM), and digital technologies, were examined as methods for optimizing halal food supply chains and ensuring sustainability. The results showed that key challenges in implementing green marketing, include supply chain inefficiencies, lack of infrastructure, and limited adoption of eco-friendly technologies by MSMEs. In conclusion, this study emphasized the importance of a collaborative approach to overcome obstacles and enhance the global competitiveness of Indonesia halal food industry, while also promoting environmental responsibility and consumer awareness.